Histopathological Evaluation of Stomach Protection by Peperomia pellucida L. in Mice with Gastroenteritis - Savitri, Lisa; Krissanjaya, Rochmad; Kasimo, Elfred Rinaldo; Juwita, Syntia Tanu; Prasetyawan, Fendy; Saristiana, Yuneka; Mebung, Konradus Klala; Amanda, Cornelia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Gastroenteritis, a widespread condition characterized by inflammation of the stomach and intestines, poses significant health challenges globally. Conventional treatments primarily focus on symptomatic relief and do not address the underlying gastric mucosal damage. Peperomia pellucida L., a medicinal plant known for its anti-inflammatory and antioxidant properties, has been suggested to possess gastroprotective effects. This study aims to evaluate the histopathological effects of P. pellucida L. on gastric protection in a mouse gastroenteritis model. Male Swiss mice were divided into six groups, receiving different treatments, including the ethanol extract of P. pellucida at varying doses (100, 300, and 500 mg/kgBW), followed by induction of gastroenteritis with Escherichia coli. Histopathological analysis was conducted to observe tissue damage across the treatment groups, including necrosis and cell degeneration. The results revealed that P. pellucida L. exhibited significant gastroprotective effects, particularly at a dose of 500 mg/kgBW, reducing gastric mucosal necrosis and inflammation compared to the control groups. The plant’s secondary metabolites, including flavonoids, tannins, saponins, and alkaloids, contributed to the observed protective effects by enhancing mucus production, reducing gastric acidity, and promoting tissue repair. These findings suggest that P. pellucida L. could be an alternative treatment for gastroenteritis and related gastric conditions, offering a natural approach to managing gastric inflammation and mucosal protection.